PENGARUH PENGUNGKAPAN SUKARELA TERHADAP NILAI PERUSAHAAN - Rusti Melyana; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
Research about voluntary disclosure nowadays has been one of the rapidly growing research areas in the accounting. Although there are many research about voluntary disclosure, but there is one issue that has not been researched sufficiently; that is the effect of voluntary disclosure on firm value. This study aims to examine the influence of voluntary disclosure on the firm value of the company. This research has been done especially in the emerging capital markets because this market have high-growth potential, but weak regulatory environment, weak corporate governance, and low information disclosure level. Sample of this study consists of 136 manufacturing companies listed on the Indonesia Stock Exchange at 2013. Data regarding voluntary disclosure level and other variables have been collected by analyzing the contents of the annul reports. The results show that the extent of voluntary disclosure is positively associated with firm value. The more voluntary information the companies disclose, the higher value they have. This finding might be accepted as a signal to companies to disclose more information to stakeholders.